2017
DOI: 10.1111/tbed.12642
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak investigations and molecular characterization of foot-and-mouth disease viruses circulating in south-west Niger

Abstract: In Niger, the epidemiological situation regarding foot-and-mouth disease is unclear since many outbreaks are unreported. This study aimed i) to identify FMDV strains currently circulating in cattle herds, and ii) to identify risk factors associated with FMD seropositive animals in clinical outbreaks. Epithelial tissues (n=25) and sera (n=227)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
2
11
1
Order By: Relevance
“…Our serological findings suggest the present or past circulation of five FMDV serotypes (O, A, SAT1, SAT2 and SAT3) in the KGR, Nigeria. These findings are consistent with previous report in Nigeria (Ehizibolo et al, ,; Ularamu et al, ), and other countries in West and Central Africa (Ludi et al, ; Souley Kouato et al, ) and should stimulate interest into increased surveillance to determine the establishment of SAT1 which recently re‐emerged (Ehizibolo et al, ) and the probable circulation of SAT3 in Nigeria. Within all HH keeping both cattle and sheep, NSP antibody positivity and serotype reactivity in SPCE detected in sheep sera corresponded with those detected in cattle suggesting an important involvement of sheep in virus circulation in livestock herds, which deserves further study.…”
Section: Discussionsupporting
confidence: 91%
“…Our serological findings suggest the present or past circulation of five FMDV serotypes (O, A, SAT1, SAT2 and SAT3) in the KGR, Nigeria. These findings are consistent with previous report in Nigeria (Ehizibolo et al, ,; Ularamu et al, ), and other countries in West and Central Africa (Ludi et al, ; Souley Kouato et al, ) and should stimulate interest into increased surveillance to determine the establishment of SAT1 which recently re‐emerged (Ehizibolo et al, ) and the probable circulation of SAT3 in Nigeria. Within all HH keeping both cattle and sheep, NSP antibody positivity and serotype reactivity in SPCE detected in sheep sera corresponded with those detected in cattle suggesting an important involvement of sheep in virus circulation in livestock herds, which deserves further study.…”
Section: Discussionsupporting
confidence: 91%
“…Recombination is believed to be dependent upon simultaneous replication of distinct viruses within the same cell, co-occupying the same replication complex. Numerous studies, especially in African countries have reported serological evidence of individual animals infected by multiple FMDV serotypes [43][44][45][46][47][48] , which highlights the common occurrence of multiple serotypes affecting herds in endemic countries. Additionally, one study in Pakistan, demonstrated detection and sequencing of two viruses from one sample with different serotypes (A and Asia-1), and another sample with two different sublineages of A/Iran-05 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported serological evidence of infection with multiple serotypes within the same animal, which indicates evidence of cumulative, lifetime exposure (Eldaghayes et al., ; Ludi et al., ; Namatovu et al., ; Sikombe et al., ; Wungak et al., ). However, simultaneous coinfection is a distinct subcategory of multiple exposures and has been reported rarely in clinical samples from cattle (Jamal, Ferrari, Ahmed, Normann, & Belsham, ; Souley Kouato et al., ; Ullah et al., ; Wungak et al., ), but is believed to occur more frequently in oropharyngeal fluid samples from African Cape buffalo (Anderson, Doughty, Anderson, & Paling, ; Hedger, ; Vosloo et al., ). An additional importance of cocirculation and coinfection lies in the ability of the distinct viruses to recombine, as demonstrated in several studies that have reported recombinant field viruses (Balinda et al., ; Jamal et al., ; Lee et al., ; Li, Shang, Liu, Liu, & Cai, ; Mohapatra et al., ).…”
Section: Introductionmentioning
confidence: 99%